Challenges of Developing the Institutional System of Public Education in the 1920’s in Hungary : - Niklai, Patrícia Dominika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
The issue of developing the institutional system of public education significantly determined the area of ​​Hungarian cultural policy in the period following the First World War. As a result of the territorial losses, the reorganization of the public education system became necessary from an administrative position, besides this, the country did not have an acceptable number of public education institutions, and even the condition of the existing schools was not satisfactory in several cases; all of this could not serve the idea of national education appropriately to the era. An identifying politician of the era was Kunó Klebelsberg, who started the building of elementary schools based on the concept of cultural supremacy to deal with the uneducated crowds and to improve the Hungarian economy through the people’s knowledge. He has initiated enormous improvements, such as the construction of thousands of new school classrooms and teachers’ apartments in just a few years, based on the Act VII of 1926 on the Establishment and Maintenance of Village Schools initiated by him.